EXAMINING THE SYMBOLIC MEANING OF AL JABBAR GRAND MOSQUE IN BANDUNG - J. Jamaludin; Imam Santosa; Juarni Anita (Journal of Islamic Architecture, 2023)
This paper discusses the formal and symbolic aesthetic meaning of the Al Jabbar Grand Mosque, a new mosque in Bandung, Indonesia, designed by Ridwan Kamil. Like Ridwan Kamil's previous works, the Al Jabbar mosque in Bandung has a contemporary design. The general concept of the architect in designing this mosque has been published in the mass media, and the public already knows the design idea of the mosque. However, there are still features within the mosque that need to be described and analyzed so that the general public can understand the architect's intention. This paper proposes answers through interpretation methods with a descriptive analysis approach to understand the symbolic meaning of the new features of the mosque. The symbolic aesthetic used in the analysis uses symbolic aesthetics from the culture of the Sundanese people, one of the ethnic groups in Indonesia, which is geographically the cultural background where the mosque was built. The analysis found that the meaning the mosque forms, apart from having a bond of meaning with the mosque, also has a bond of meaning with the local culture. The architect made it differently with the spirit of novelty to enrich Islamic architecture and design treasures.